Understanding the transmission dynamics of Escherichia coli O157:H7 super-shedding infections in feedlot cattle - Antaki-Zukoski,Elizabeth M.; Li,Xunde; Hoar,Bruce; Adaska,John M.; Byrne,Barbara A.; Atwill,Edward R. (PeerJ, 2021)
Background The presence of Escherichia coli O157:H7 (E. coli O157:H7) super-shedding cattle in feedlots has the potential to increase the overall number (bio-burden) of E. coli O157:H7 in the environment. It is important to identify factors to reduce the bio-burden of E. coli O157 in feedlots by clarifying practices associated with the occurrence of super-shedders in feedlot cattle. Methods The objective of this study is to (1) identify host, pathogen, and management risk factors associated with naturally infected feedlot cattle excreting high concentrations of E. coli O157:H7 in their feces and (2) to determine whether the ingested dose or the specific strain of E. coli O157:H7 influences a super-shedder infection within experimentally inoculated feedlot cattle. To address this, (1) pen floor fecal samples and herd parameters were collected from four feedlots over a 9-month period, then (2) 6 strains of E. coli O157:H7, 3 strains isolated from normal shedder steers and 3 strains isolated from super-shedder steers, were inoculated into 30 one-year-old feedlot steers. Five steers were assigned to each E. coli O157:H7 strain group and inoculated with targeted numbers of 102, 104, 106, 108, and 1010 CFU of bacteria respectively. Results In the feedlots, prevalence of infection with E. coli O157:H7 for the 890 fecal samples collected was 22.4%, with individual pen prevalence ranging from 0% to 90% and individual feedlot prevalence ranging from 8.4% to 30.2%. Three samples had E. coli O157:H7 levels greater than 104 MPN/g feces, thereby meeting the definition of super-shedder. Lower body weight at entry to the feedlot and higher daily maximum ambient temperature were associated with increased odds of a sample testing positive for E. coli O157:H7. In the experimental inoculation trial, the duration and total environmental shedding load of E. coli O157:H7 suggests that the time post-inoculation and the dose of inoculated E. coli O157:H7 are important while the E. coli O157:H7 strain and shedding characteristic (normal or super-shedder) are not. Discussion Under the conditions of this experiment, super-shedding appears to be the result of cattle ingesting a high dose of any strain of E. coli O157:H7. Therefore strategies that minimize exposure to large numbers of E. coli O157:H7 should be beneficial against the super-shedding of E. coli O157:H7 in feedlots.
Keywords: Escherichia coli O157:H7; Feedlot cattle; Super-shedders; Strain; Ingested dose; Bio-burden